PENTINGNYA SUPLEMEN TABLET BESI BAGI PENINGKATANKADAR HEMOGLOBIN PADA REMAJA PUTRI - Rr. Catur Leni Wulandari; Yuli Fitriasih (Majalah Ilmiah Sultan Agung, 2014)
Adolescence is a time of transition from childhood to adulthood who have all the development of all aspects/ functions to enter adulthood. At this time they are not children of both of form and of a way of thinking or acting, but not too mature adults. Teenage years were in the range 12-23 years.Young women prone to malnutrition in the peak period of growth and development which is both less intake of nutrients due to wrong diet , the influence of the social environment (want to trim). Lack of iron and other nutrients essential for growth and development (zinc) will result in often sickly. So that the necessary improvement of the nutritional status of young women that were able to go through the process of optimal growth and development. To get qualified young generation, to consider health status, not only free of the disease but also a source of creative and productive power.Impact of anemia in adolescent girls during the growth of the body that is easily infected, resulting in a fitness/ body fitness is reduced, the spirit of learning/ achievement decreased, so that at the time would be mothers with high -risk situation.Keywords : iron supplement tablets , hemoglobin levels, teenage daughter